Normal deglutitive responses of the human lower oesophageal sphincter. Issue 5 (May 1972) - Kaye, Michael D.; Showalter, J. Philip
Abstract : The responses to deglutition of the lower oesophageal high pressure zone were studied in 13 healthy subjects. The recording assembly included three perfused pressure recording catheters, whose recording orifices were at the same axial level, and a more distally situated p H electrode. Relaxation and contraction progressed in a sequential fashion along the length of the high pressure zone. At the time of maximum relaxation, a small pressure gradient, which was greatest at a point approximately 1 cm distal to the pressure inversion point, was maintained between stomach and oesophagus. The frequency of post-deglutitive contractions in the high pressure zone, which were observed to occur distal to the pressure inversion point in all subjects, steadily increased as the recording assembly was withdrawn proximally. The amplitude of such contractions was greater in the high pressure zone than in the distal oesophagus. There was a significant correlation between maximum resting pressure and amplitude of contractions within the high pressure zone. The proper assessment of the function of the high pressure zone should include consideration of the spatiotemporal relationships of pressure events within the lower oesophagus and the high pressure zone, in addition to measurements of their absolute dimensions. The p H electrode measurements, performed after the intragastric instillation of at least 150 ml of 0·1 N HCl, showed transient falls in the p H of the distal high pressure zone after deglutition in all subjects. These p H responses decreased in frequency as the p H electrode was withdrawn proximally, and did not occur in the non-sphincteric oesophagus. It would appear therefore that although gastroesophageal competence is retained during swallowing, the mucosal lining of the greater part of the high pressure zone is briefly exposed to gastric contents for a few seconds after deglutition.